Teste de tetrazólio em sementes de Copaifera langsdorffii E schizolobium parahyba - Fogaça, Cristiane Alves; Krohn, Nádia Graciele; de Aquino Souza, Márcio; de Paula, Rinaldo César [UNESP] (My University, 2011)
This research aimed to standardize the tetrazolium test for evaluation of viability of Copaifera langsdorffii Desf. and Schizolobium parahyba Vell. Blake seeds. It evaluated the following methodologies: seeds scarificated mechanically and soaked up by 24 and 48 hours, with posterior seed coat removal and immersed in tetrazolium solution at 0.075; 0.10 and 0.20% for 2, 3 and 4 hours, 35 °C, the dark one. The evaluated methodologies that had been efficient in the attainment of satisfactory coloration, allowing the differentiation of tissues, and in the evaluation of the physiological quality of the seeds when compared with the germination test, had been: for the species Copaifera langsdorffii, seeds scarificated and soaked up by 24 hours, 35 °C, with posterior seed coat removal, submitted to the tetrazolium solution 0.20% for 4 hours, 35 °C, in the dark one, and for the species guapuruvu, seeds scarificated and soaked up by 48 hours, 35 °C, with posterior seed coat removal, submitted to the tetrazolium solution 0.10% for 4 hours, 35 °C, in the dark one.
Tetrazolium test in Copaifera langsdorffii and Schizolobium parahyba seeds
Keywords: Copaifera langsdorffii; Fast test; Forest seeds; Schizolobium parahyba